2018
DOI: 10.1136/sextrans-2017-053480
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium: high prevalence of resistance to macrolides and frequent anorectal infection in men who have sex with men in western Sydney

Abstract: We demonstrated a high prevalence of and very high levels of macrolide resistance among MSM attending WSSHC. Our findings support the routine use of an assay to detect macrolide resistance mutations in infections. This will ensure, in regions or populations with high rates of macrolide resistance among strains, that first-line treatment with azithromycin will only be used if a macrolide-sensitive strain is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 21 publications
6
58
6
1
Order By: Relevance
“…In our study, 60% and 30% of 20 strains showed mutations associated with macrolide and quinolone resistance, and 25% with both. Prevalence of macrolide resistance of M. genitalium may now exceed 50% [3,24] and is reported to be even higher in HIV-positive patients [25] or HIV-PrEP users [26,27], which corresponds to our results. The study from Germany calculated a rate of 80% macrolide-resistant strains [22].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 60% and 30% of 20 strains showed mutations associated with macrolide and quinolone resistance, and 25% with both. Prevalence of macrolide resistance of M. genitalium may now exceed 50% [3,24] and is reported to be even higher in HIV-positive patients [25] or HIV-PrEP users [26,27], which corresponds to our results. The study from Germany calculated a rate of 80% macrolide-resistant strains [22].…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis found much lower prevalence estimates for MSM of 3.2% in five community-based studies from Australia and Central America and 3.7% in four clinic-based studies from Europe and the US [35]. Other studies found MG prevalences between 2.0 and 13.4%, and differed in the number of tested sites, clinical status, and reported sexual behavior [36][37][38][39][40][41][42].…”
Section: Sti Prevalencesmentioning
confidence: 97%
“…HIV-participants were significantly younger than HIV+ MSM (median 35 IQR [30][31][32][33][34][35][36][37][38][39][40][41][42][43] vs. 44 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], p < 0.01) and less likely to be born in Germany (67.2% vs. 80.8%, p < 0.01), but they were more likely to have acquired university-entrance diploma (74.6% vs. 54.4%, p < 0.01). The median number of male sex partners was significantly higher in HIV-MSM than in HIV+ (6 [3][4][5][6][7][8][9][10][11][12][13][14][15] vs. 4 [1][2][3][4]…”
Section: Demographic Characteristics and Sexual Behaviour Of The Studmentioning
confidence: 99%
“…In the UK, interest was galvanised in 2015 by data from the third National Survey of Health Attitudes and Lifestyles (NATSAL 3). But studies brought together of STI show us how identical issues are having to be addressed in Australia1 and two regions of the US 2 3. Everywhere there is the same challenge of defining universal standards for screening and management.…”
mentioning
confidence: 99%
“…Taylor et al 3 pursue the implications of MG for women’s reproductive health, analysing the association with histological endometritis, an a signal of pelvic inflammatory disease. Couldwell et al 1 address antibiotic resistance in an Australian MSM population, investigating mutations of the organism linked to macrolide resistance.…”
mentioning
confidence: 99%